Quasi-Talbot effect of orbital angular momentum beams for generation of optical vortex arrays by multiplexing metasurface design. Issue 2 (14th December 2017) - Gao, Hui; Li, Yang; Chen, Lianwei; Jin, Jinjin; Pu, Mingbo; Li, Xiong; Gao, Ping; Wang, Changtao; Luo, Xiangang; Hong, Minghui
Abstract : The quasi-Talbot effect of orbital angular momentum (OAM) beams, in which the centers are placed in a rotationally symmetric position, is demonstrated both numerically and experimentally for the first time. Abstract : The quasi-Talbot effect of orbital angular momentum (OAM) beams, in which the centers are placed in a rotationally symmetric position, is demonstrated both numerically and experimentally for the first time. Since its multiplication factor is much higher than the conventional fractional Talbot effect, the quasi-Talbot effect can be used in the generation of vortex beam arrays. A metasurface based on this theory was designed and fabricated to test the validity of this assumption. The agreement between the numerical and measured results suggests the practicability of this method to realize vortex beam arrays with high integrated levels, which can open a new door to achieve various potential uses related to optical vortex arrays in integrated optical systems for wide-ranging applications.